PARTAI POLITIK DALAM PERSPEKTIF ISLAM - Hasanuddin Yusuf Adan (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2014)
A political party is a tool for human person or group of people to reach the power that can be set in accordance with the provisions of the country in the political parties. Originally Islam does not recognize political parties in determining the executive and state power, but in tune with the times difficult for Muslims who inhabit countries today to not wear a political party in control and manage the state. Islamic political experts differ between one another with respect to whether or not the state should Muslim majority wear and use political parties as one of the attributes of the state, they allow and others do not. Eventgouh conditions and situations often affect to something new that matters dealing with Islam and Muslims. In this age where the world is ruled by non-Muslim world institutions of the United Nations (UN) then be mistaken for Muslims not to accept and use the political parties in the Muslim majority country. The most important note in the atmosphere as it is the practice of the Muslims belong to a party must not follow the practice of non-Muslims who justify the means. Islamic Ummah must maintain originality of morality in politics so that the political party that sponsored the non-Muslims in Muslim practice became Islamic. Kata Kunci: Partai, politik, perspektif, Islam